แนวทางการพัฒนารูปแบบการปฏิบัติงานที่บ้าน ในสถานการณ์การแพร่ระบาดของโรคติดเชื้อไวรัสโคโรนา 2019 (โควิด - 19) ของเจ้าหน้าที่สำนักงานการประปาส่วนภูมิภาค จังหวัดอุดรธานี - Kaewsuporn, Nutchanon; Butrudom, Thanawit (Journal of Graduate School Sakon Nakhon Rajabhat University, 2023)
The objectives of this research were to 1) examine the relationship between home working conditions and staff performance, 2) determine factors affecting home working conditions on staff performance, and 3) establish guidelines for developing a work-from-home performance model for staff. This research used a quantitative approach. Research guidelines were also developed using a qualitative research approach. The collecting data from the questionnaire and interviews were analyzed and summarized to validate the accuracy. The findings revealed that the home working conditions and staff performance at the Provincial Waterworks Authority Office, Mueang District, Udon Thani Province featured all factors at a high level and all of which had considerable room for improvement. The office took measures to ensure that staff was equipped to manage any potential issues. Despite some minor performance issues when transitioning to remote work during the coronavirus disease 2019 outbreak, the staff made necessary adjustments to their task performance to accommodate the transition, such as acquiring new skills to ensure efficient individual performance. The most critical factors for staff performance comprised several factors, such as job-related independence, diversity of skills, work environment, work reflection, quality of working equipment, work values, and workload.